2015
DOI: 10.5455/njppp.2015.5.2308201563
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin improved spatial memory dysfunctions in rat model of intracerebroventricular streptozotocin-induced sporadic Alzheimer's disease

Abstract: Background: Alzheimer's disease (AD) is one of the most common neurodegenerative syndromes characterized by a progressive decline in the spatial memory. There are convincing evidences on the neuroprotective effects of flavonoids against AD. Aims and Objective: To determine the effect of quercetin on the acquisition and retention of spatial memory in a rat model of AD. Materials and Methods: Twenty-four male Wistar rats were divided into four groups (six in each): group I: control rats receiving intracerebroven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 21 publications
1
13
0
2
Order By: Relevance
“…To do so, EVR was intraperitoneally (ip) injected to AD rats on days 21-28 post-STZ injection, one hour before the behavioral study. As our preliminary experiments, along with other studies, showed that learning and memory impairments were established at day 21 post-STZ administration (Ashrafpour et al, 2015[ 5 ]; Mehla et al, 2013[ 50 ]; Salkovic-Petrisic et al, 2013[ 67 ]). Experiment II was carried out to evaluate the effect of the mTORC1 inhibitor on the progress of Alzheimer's disease (groups 1, 2, 5-7).…”
Section: Methodssupporting
confidence: 72%
“…To do so, EVR was intraperitoneally (ip) injected to AD rats on days 21-28 post-STZ injection, one hour before the behavioral study. As our preliminary experiments, along with other studies, showed that learning and memory impairments were established at day 21 post-STZ administration (Ashrafpour et al, 2015[ 5 ]; Mehla et al, 2013[ 50 ]; Salkovic-Petrisic et al, 2013[ 67 ]). Experiment II was carried out to evaluate the effect of the mTORC1 inhibitor on the progress of Alzheimer's disease (groups 1, 2, 5-7).…”
Section: Methodssupporting
confidence: 72%
“…The antioxidant effect of P. guajava fruit might also be beneficial in protecting the brains of rodents against oxidative stress [50]. A previous study confirmed the effect of quercetin on the acquisition and retention of spatial memory in a rat model of Alzheimer's disease and concluded that there is convincing evidence on the neuroprotective effects of flavonoids against Alzheimer's disease [51]. According to the studies cited above, P. guajava leaves contain quercitin.…”
Section: Discussionmentioning
confidence: 95%
“…However, quercetin (500 mg/day) administration for 12 weeks failed to exhibit a significant effect on neurocognitive functioning in humans, raising concern the clinical translation of results from in vitro and in vivo animal studies [63]. Quercetin enhanced the spatial memory in aged and ethanol intoxicated mice through it antioxidant and scavenging properties [64]. Mohammadi, et al (2014) reported that quercetin alleviated the deleterious effects of chronic stress on learning and memory in rats, improving its cognitive deficit by suppressing the oxidative stress and plasma corticosterone level.…”
Section: Discussionmentioning
confidence: 99%